LITERASI KEUANGAN SYARIAH PEKERJA MIGRAN INDONESIA: PELATIHAN PENDIRIAN BAITUL MAL WAT-TAMWIL DI BRUNEI DARUSSALAM - Mustikasari, Molly; Mulyasari, Heni; Haryadi, Yudi; Fitriyani, Nida (Institut Teknologi Garut, 2025)
Indonesian Migrant Workers (PMI) in Brunei Darussalam face various economic challenges, including low sharia financial literacy, less than optimal financial management, and limited access to formal financial services. This study aims to improve PMI's sharia financial literacy through training in establishing Baitul Maal Wat-Tamwil (BMT) as a sustainable economic solution for 15 members of the Indonesian Community Association (PERMAI). The method used is interactive online and offline training that includes material delivery, simulations, and technical assistance in establishing and managing BMT. The results of the training showed that participants gained an understanding of the concept of sharia finance, financial planning, and management of community-based financial institutions. This program also opens up opportunities for PMI to build economic independence and strengthen social networks in their environment. With this approach, it is hoped that similar training models can be applied in other PMI communities abroad